2022
DOI: 10.1371/journal.pone.0266304
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genomes and phylogeny in three Euterpe palms (E. edulis, E. oleracea and E. precatoria) from different Brazilian biomes

Abstract: The Brazilian palm fruits and hearts-of-palm of Euterpe edulis, E. oleracea and E. precatoria are an important source for agro-industrial production, due to overexploitation, conservation strategies are required to maintain genetic diversity. Chloroplast genomes have conserved sequences, which are useful to explore evolutionary questions. Besides the plastid DNA, genome skimming allows the identification of other genomic resources, such as single nucleotide polymorphisms (SNPs), providing information about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…All four repeat types (palindrome, forward, reverse and complementary) are present in the chloroplast genome. The results are consistent with repeat types of three other palm family of genus Euterpe ( Francisconi et al, 2022 ) in which palindrome repeat has the highest number, followed by forward repeat, reverse repeat and finally complementary repeat. This revealed high conservation of gene structure in palm species specifically among genus Euterpe and Elaeis species.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All four repeat types (palindrome, forward, reverse and complementary) are present in the chloroplast genome. The results are consistent with repeat types of three other palm family of genus Euterpe ( Francisconi et al, 2022 ) in which palindrome repeat has the highest number, followed by forward repeat, reverse repeat and finally complementary repeat. This revealed high conservation of gene structure in palm species specifically among genus Euterpe and Elaeis species.…”
Section: Discussionsupporting
confidence: 87%
“…Both studies ( Uthaipaisanwong et al, 2012 ; Yao et al, 2023 ) showed the gene content and arrangement in chloroplast genome are highly conserved in the palm family. Comparative analysis of chloroplast genomes was done between three different palm species from Brazil ( Francisconi et al, 2022 ). This study showed these three species’ nucleotide sequences are significantly varied from each other in term of insertion/deletion (InDels) and single nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%
“…In all species, the mononucleotide A/T was the most frequent motif. This characteristic was also reported in other palm complete chloroplast genomes 30,31,33 . Plastid SSR markers, especially combined with nuclear markers, can improve the e ciency of studies of structure, diversity and gene ow in natural populations 37 .…”
Section: Discussionsupporting
confidence: 85%
“…2) 31 . As already pointed out, a signi cant dissimilarity among the species of the subfamily Arecoideae that occurs in Brazil can be identi ed in the length of the LSC, between 40,000 and 50,000 bp 33 . Furthermore, between the species C. alba and C. prunifera of the subfamily Coryphoideae, it was also possible to observe a reduction in LSC size (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation